2021
DOI: 10.1038/s41598-021-02069-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pollution levels of potential toxic elements in urban vegetable gardens in southwest China

Abstract: Vegetable gardens are increasingly common in urban areas and can provide numerous societal benefits; however, contamination with potential toxic elements (PTEs) due to urbanization and industrialization is cause for concern. The present study aimed to assess the source of contamination and pollution levels in urban garden soils, as well as the health risks for adults and children consuming vegetables grown in such environments. Various types of vegetable samples and their corresponding soils from 26 community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…Pb residues are found in both industrial and residential soils, and are transferred to, and accumulated in plants ( Doris et al., 2021 ; Gao et al., 2021 ). Pb is known to cause chlorosis, oxidative stress, and growth and development disorders in plant leaves ( Kanwal et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pb residues are found in both industrial and residential soils, and are transferred to, and accumulated in plants ( Doris et al., 2021 ; Gao et al., 2021 ). Pb is known to cause chlorosis, oxidative stress, and growth and development disorders in plant leaves ( Kanwal et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the Pb content in soils approximately 20 kilometers away from the La Oroya metallurgical complex in Peru was 217.81 ± 39.48 mg/kg, of which 9.5% was transferred to the surrounding grasses (Doris et al, 2021). The Pb content in lettuce leaves and Chinese cabbage grown in urban garden soils reached 0.05 mg/kg fresh weight, and the Pb concentration in these vegetables was positively correlated with the Pb soil levels (Gao et al, 2021;Calabro ́et al, 2022). The over-standard rate of Pb in 673 plant samples provided by a typical intensive production system in Hainan Province is 2.67%, and leafy vegetables are more polluted than non-leafy vegetables (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Pb residues were found in both industrial and human living soils, which will be further transferred to plants to accumulate (Doris, Jorge et al, Gao, Zhang et al 2021). A study reported that Pb can cause chlorosis, oxidative stress and growth and development disorders in plant leaves ).…”
Section: Discussionmentioning
confidence: 99%
“…In urban garden soil planting leafy vegetables, the Pb content in lettuce leaves and Chinese cabbage reached 0.05 mg/kg FW and found that the metal concentration in vegetables was positively correlated with the metal consistence in the soil (Gao, Zhang et al 2021). The over-standard rate of Pb in the 673 plant samples provided by the typical intensive production system in Hainan Province is 2.67%, and leafy vegetables have a higher degree of pollution than non-leaf vegetables (Yang, Wang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Soil contaminated with heavy metals such as chromium further degrade the quality of agricultural crops growing on them and pose a potential threat to human food security. Previous research has suggested that excessive chromium levels severely affected crops of sweet potatoes ( Ipomoeabatatas ) (Gao et al, 2021 ) and wheat ( Triticum aestivum ) (Wang et al, 2017 ), and studies on heavy metals have revealed that the threat of chromium contaminated soil is imminent ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%